Elderly digital surfing: the influence of family support on media usage behaviour / Shen Shuaizhi …[et al.] - Shuaizh, Shen; Abdul Aziz, Ahlam; Ibnu, Ireena Nasiha; Qi, Sun (Faculty of Communication and Media Studies (FCMS), 2024)
This study employed the theory of planned behavior theory model to explore the impact of family support on the digital media usage of older adults. Structural equation model was utilized for the analysis. Using Guangdong Province as the sampling frame, 416 valid samples were collected through cooperation with residents' committees using purposive sampling methods. The data analysis indicated that there were significant positive correlations among elderly family support, media attitudes, self-efficacy, and media behavior. However, family support did not directly predict digital media usage behavior among the elderly. Instead, family support positively predicted media attitude and self-efficacy among the elderly. Additionally, the elderly media attitude and self-efficacy mediated the relationship between family support and digital media usage behavior. Family support indirectly influences digital media usage behavior through its effects on shaping attitudes and beliefs about media and one's abilities to use it effectively.